Full-industrial solid waste filling material based on phosphogypsum

By mixing industrial solid waste such as phosphogypsum, fly ash, blast furnace slag and calcium carbide slag with liquid polycarboxylic acid water reducing agent, suspension stabilizer and water, a filling material that meets the requirements of overlayed rock filling or filling mining is prepared, which solves the problems of high energy consumption, carbon emissions and high costs in low utilization rate of industrial solid waste and cement cement filling technology, and achieves low-cost, environmentally friendly and efficient mine filling effects.

CN119822768APending Publication Date: 2025-04-15SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411777059.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The low utilization rate of existing industrial solid waste and the high energy consumption, carbon emissions and high costs in cement cement filling technology have led to limited application of industrial solid waste in mine filling.

Method used

A full industrial solid waste filling material based on phosphogypsum was designed. By mixing industrial solid waste such as phosphogypsum, fly ash, blast furnace slag and calcium carbide slag with liquid polycarboxylic acid water reducing agent, suspension stabilizer and water, filling materials that meet the requirements of radial filling or filling mining of rocks were prepared.

Benefits of technology

It has realized low-cost, environmentally friendly and efficient mine filling solutions, significantly improved the utilization rate of industrial solid waste, reduced carbon emissions, and met the requirements of mechanical strength and liquidity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822768A_ABST
    Figure CN119822768A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphogypsum-based full industrial solid waste filling material which is prepared from a solid component and a liquid component, the solid component comprises phosphogypsum, fly ash, blast furnace slag and carbide slag, and the liquid component comprises a liquid polycarboxylate superplasticizer, a suspension stabilizer and water. According to the full-industrial solid waste filling material based on phosphogypsum, bulk industrial solid waste is adopted as the main raw material, the bleeding rate of an obtained filling body is smaller than 5%, the fluidity is larger than 18 cm, the unconfined compressive strength in 28 days exceeds 3000 kPa, the initial setting time is 25-40 h, and the specified standard of mine backfilling application is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental protection, and in particular relates to a full-industrial solid waste filling material based on phosphogypsum. Background Art

[0002] Industrial solid waste refers to solid waste generated in industrial production activities, which are various waste residues, dust and other wastes discharged into the environment during industrial production. At present, typical industrial solid wastes mainly include the following three categories: alkaline solid wastes, sulfate solid wastes and silicon-aluminum solid wastes. For example, the low utilization rate of industrial solid wastes such as red mud, phosphogypsum and carbide slag has become the main constraint on the green and safe development of industries such as mining, metallurgy and chemical industry.

[0003] As an environmentally friendly mining technology, cement bonding filling technology has been widely used in underground mining. Cement bonding filling technology involves preparing a mixture that includes a specific proportion of solid waste, gelling agent, water and other additives to meet the strength required for filling the goaf. In order to promote the use of phosphogypsum, a study has proposed a method of using phosphogypsum for cement bonding filling to significantly increase the consumption of phosphogypsum. This technology uses phosphogypsum as a filling aggregate and prepares a filling material that meets the filling strength requirements of the goaf by adding about 10% of cement.

[0004] However, the production process of cement is accompanied by high energy consumption and significant carbon dioxide emissions, which accelerates the global greenhouse effect. In addition, when cement is used as a gelling agent in cementitious filling technology, its cost accounts for about 70-80% of the overall cost. Therefore, it has become a trend to partially or completely replace cement with low-carbon, environmentally friendly, and cost-effective industrial solid waste. However, the phosphogypsum cement cementitious filling technology based on the resource utilization of industrial solid waste faces many challenges, such as high water seepage rate, easy sedimentation, long curing time, and pipeline blockage. So far, no systematic research has been conducted, resulting in a lack of field application reports of this technology.

[0005] Therefore, the present invention designs a fully industrial solid waste filling material based on phosphogypsum whose working characteristics and mechanical properties meet the requirements of overburden separation filling or filling mining, so as to provide a more economical and environmentally friendly mine filling solution, achieve a win-win situation of economic and environmental benefits, and is of great significance. Summary of the invention

[0006] One of the objects of the present invention is a full industrial solid waste filling material based on phosphogypsum, which is made of a solid component and a liquid component, wherein the solid component includes phosphogypsum, fly ash, blast furnace slag and carbide slag, and the liquid component includes a liquid polycarboxylate water reducer, a suspension stabilizer and water;

[0007] Among them: the mass ratio of phosphogypsum, fly ash, blast furnace slag and carbide slag is (65-80):(5-20):(5-20):10, the mass ratio of liquid polycarboxylic acid water reducer to solid component is 0.4:100, the mass ratio of suspension stabilizer to solid component is (0.04-0.18):100, and the mass ratio of water to solid component is (35-50):100.

[0008] Furthermore, the content of CaSO4·H2O in the phosphogypsum is ≥65%, and the pH value is ≤4; the content of SiO2 and Al2O3 in the fly ash is ≥80%; the content of CaO in the blast furnace slag is ≥40%, and the content of SiO2 is ≥30%; the content of CaO in the carbide slag is ≥85%, and the pH value is ≥12.

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned all-industrial solid waste filling material, comprising the following steps:

[0010] Step 1, drying and crushing the phosphogypsum to obtain phosphogypsum powder; air-drying fly ash, blast furnace slag, and carbide slag to obtain dry fly ash, granulated blast furnace slag, and carbide slag powder;

[0011] Step 2: premixing the phosphogypsum powder, fly ash, granulated blast furnace slag and carbide slag powder obtained in step 1 to obtain a solid component;

[0012] Step 3, mixing a liquid polycarboxylate water reducer, a suspension stabilizer and water to obtain a liquid component;

[0013] Step 4, mixing the solid component obtained in step 2 and the liquid component obtained in step 3 to obtain a full industrial solid waste filling material based on phosphogypsum.

[0014] Furthermore, in step 1, the phosphogypsum is dried at 45°C.

[0015] The third object of the present invention is to provide the application of the above-mentioned all-industrial solid waste filling material in overburden rock separation filling or filling mining.

[0016] In order to alleviate the problem of low utilization rate of bulk industrial solid waste mainly composed of phosphogypsum, and provide a safe and reliable filling material for overburden separation layer filling or filling mining, the present invention designs a filling material prepared by using phosphogypsum, fly ash, blast furnace slag and carbide slag as main raw materials. The filling material makes full use of the physical and chemical properties of different industrial solid wastes, has low cost and stable performance, and can consume a large amount of bulk industrial solid waste while meeting the requirements of overburden separation layer filling or filling mining.

[0017] The water seepage rate of the all-industrial solid waste filling material of the present invention is less than 5%, the fluidity is greater than 18 cm, and the initial setting time is 25-40 hours; after curing for 28 days under standard curing conditions (temperature is 20±2° C., relative humidity is above 95%), the unconfined compressive strength of a cylindrical specimen with a diameter of 50 mm and a height of 100 mm is greater than 2000 kPa;

[0018] Compared with the existing phosphogypsum cementing filling material using cement or cement clinker as the main cementing material, the present invention has the following advantages:

[0019] 1. After 5-10 minutes of mixing and stirring in step 4, the pH value of the filling material is immediately recorded. At this time, the pH value is over 12.5. Under standard curing conditions (temperature of 20±2°C and relative humidity of more than 95%), the pH value drops rapidly after 3 days of curing, but with the increase of curing time, the rate of pH drop gradually slows down, and the pH value exceeds 10 after 60 days. This alkalinity is essential for promoting the pozzolanic reaction involving blast furnace slag and fly ash. Under highly alkaline conditions, the disintegration of the pozzolanic lattice leads to the dissolution of amorphous alumina and silica components in blast furnace slag and fly ash. Therefore, this process produces a rich Si and Al ions as well as Ca produced by the ionization of carbide slag during hydration. 2+ and OH - ion environment, as shown in formula (1). Under the alkalinity and chemical composition conditions of the system, the so-called pozzolanic reaction (formulas (2), (3) and (4)) can occur to form compounds similar to those in Portland cement slurry, such as calcium silicate hydrate (CSH), calcium aluminate (CAH) and calcium aluminosilicate (CASH). In addition, phosphogypsum dissolves in an alkaline environment, providing a large amount of sulfate ions, which promotes the forward reaction (5), thereby forming a large amount of calcium aluminate (Aft). The formation of AFt promotes strength. The formation of these products jointly contributes to the long-term mechanical strength of the all-industrial solid waste filling material based on phosphogypsum.

[0020] CaO + H2O → Ca(OH)2 → Ca 2+ + 2OH - (1)

[0021] Ca 2+ + 2OH - + SiO2 → CSH (2)

[0022] Ca 2+ + 2OH - + Al2O3 → CAH (3)

[0023] Ca 2+ + 2OH- + Al2O3 + SiO2 → CASH (4)

[0024] 3CaSO4 + 3CaO·Al2O3 + 32H2O →3CaO·Al2O3·3CaSO4·32H2O (5)

[0025] 2. The initial setting time of the all-industrial solid waste filling material based on phosphogypsum prepared by the present invention is 25 to 40 hours, and the final setting time is 35 to 50 hours. This is significantly improved compared with the initial setting time and final setting time of the phosphogypsum cemented filling body using cement or cement clinker as a binder. This improvement not only promotes the development of the early strength of the filling material, but also ensures that it maintains fluidity and workability during transportation, reduces the possibility of coagulation and pipeline blockage during the transportation stage, and thus improves the efficiency and reliability of the backfill process.

[0026] 3. The 28-day unconfined compressive strength of the all-industrial solid waste filling material based on phosphogypsum prepared by the present invention is ≥2000kPa, and the fluidity is ≥250mm at 170mm, which can meet the requirements of "GB / T 39489-2020 Technical Specification for Full Tailings Paste Filling".

[0027] 4. The water seepage rate of the all-industrial solid waste filling material based on phosphogypsum prepared by the present invention is ≤5%, which meets the requirement proposed by relevant scholars that the water seepage rate of the filling paste should be maintained in the range of 1.5% to 5%.

[0028] 5. The all-industrial solid waste filling material based on phosphogypsum prepared by the present invention can effectively absorb industrial by-products, which not only reduces the filling cost, but also promotes waste recycling and resource conservation, while reducing carbon emissions, providing support for clean production and sustainable development. The material realizes the concept of "waste treatment with waste", meets the requirements of green circular low-carbon economic development, and provides an effective solution for the resource utilization of industrial solid waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image magnified 5000 times of the all-industrial solid waste filling material based on phosphogypsum prepared with a curing age of 28 days in Example 1 of the present invention.

[0030] Figure 2 This is a SEM image magnified 5000 times of the all-industrial solid waste filling material based on phosphogypsum prepared with a curing age of 28 days in Example 2 of the present invention. DETAILED DESCRIPTION

[0031] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.

[0032] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0033] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0034] Example 1

[0035] A method for preparing a full industrial solid waste filling material based on phosphogypsum comprises the following steps:

[0036] Step 1, placing the raw material phosphogypsum from Yichang, China in a constant temperature drying environment of 45°C, drying and crushing it with a soil crusher to obtain phosphogypsum powder; air-drying fly ash from Shandong, China, blast furnace slag and carbide slag from Henan, China, respectively, to obtain dry fly ash, granulated blast furnace slag and carbide slag powder. The chemical compositions of the four industrial solid wastes are shown in Table 1. Liquid polycarboxylate water reducer and suspension stabilizer (FK-X type) were purchased from Shanxi Feike New Material Technology Co., Ltd.

[0037] Table 1 Chemical composition of four industrial solid wastes

[0038]

[0039] Step 2, take 6500g of phosphogypsum, 1750g of fly ash, 750g of blast furnace slag, and 1000g of carbide slag in step 1, pour them into a cement mortar mixer and stir for 10 minutes to premix to obtain a solid mixture.

[0040] Step 3, take 3500 g of tap water, 40 g of liquid polycarboxylate water reducer, and 18 g of suspension stabilizer, mix and stir for 10 minutes to obtain a liquid mixture.

[0041] Step 4, pouring the liquid mixture obtained in step 3 into a cement mortar mixer, mixing and stirring for 10 minutes, to obtain a full industrial solid waste filling material based on phosphogypsum.

[0042] Take a certain amount of filling material for setting time, fluidity and water bleeding test, transfer the remaining filling material to a cylindrical plastic mold with a diameter of 50mm and a height of 100mm, and drill a hole with a diameter of 2mm at the bottom of each mold. Then place the mold on a vibration table for 120 seconds and wrap it with plastic film. After a 24-hour pre-setting period, the sample is carefully removed from the mold and wrapped with plastic film to retain moisture. Subsequently, all samples are transferred to a laboratory with a stable temperature and humidity environment (maintained at 20±2℃ and 90±5%, respectively) for curing for 28 days.

[0043] The filling material obtained in this embodiment was tested for setting time, fluidity and water seepage rate, and the fluidity was measured to be 18.5 cm, the initial setting time was 27.5 h, the final setting time was 36.5 h, the water seepage rate was 2.14%, and the 28-day unconfined compressive strength was 3511.79 kPa.

[0044] Example 2

[0045] A method for preparing a full industrial solid waste filling material based on phosphogypsum comprises the following steps:

[0046] Step 1: Place the raw material phosphogypsum from Yichang, China in a constant temperature drying environment at 45°C, dry it, and crush it with a soil crusher to obtain phosphogypsum powder; air-dry the fly ash from Shandong, China, blast furnace slag and carbide slag from Henan, China, to obtain dry fly ash, granulated blast furnace slag and carbide slag powder. The chemical compositions of the four industrial solid wastes are shown in Table 1.

[0047] Step 2, take 7000g of phosphogypsum, 1000g of fly ash, 1000g of blast furnace slag and 1000g of calcium carbide slag in step 1, pour them into a cement mortar mixer and stir for 10 minutes to premix to obtain a solid mixture.

[0048] Step 3, take 3500 g of tap water, 40 g of liquid polycarboxylate water reducer, and 18 g of suspension stabilizer, mix and stir for 10 minutes to obtain a liquid mixture.

[0049] Step 4, pouring the liquid mixture obtained in step 3 into a cement mortar mixer, mixing and stirring for 10 minutes, to obtain a full industrial solid waste filling material based on phosphogypsum.

[0050] Take a certain amount of filling material for setting time, fluidity and water bleeding test, transfer the remaining filling material to a cylindrical plastic mold with a diameter of 50mm and a height of 100mm, and drill a hole with a diameter of 2mm at the bottom of each mold. Then place the mold on a vibration table for 120 seconds and wrap it with plastic film. After a 24-hour pre-setting period, the sample is carefully removed from the mold and wrapped with plastic film to retain moisture. Subsequently, all samples are transferred to a laboratory with a stable temperature and humidity environment (maintained at 20±2℃ and 90±5%, respectively) for curing for 28 days.

[0051] The filling material obtained in this embodiment was tested for setting time, fluidity and water seepage rate, and the fluidity was measured to be 19.0 cm, the initial setting time was 29.0 h, the final setting time was 386.5 h, the water seepage rate was 2.85%, and the 28-day unconfined compressive strength was 3233.47 kPa.

[0052] Example 3

[0053] A method for preparing a full industrial solid waste filling material based on phosphogypsum comprises the following steps:

[0054] Step 1: Place the raw material phosphogypsum from Yichang, China in a constant temperature drying environment at 45°C, dry it, and crush it with a soil crusher to obtain phosphogypsum powder; air-dry the fly ash from Shandong, China, blast furnace slag and carbide slag from Henan, China, to obtain dry fly ash, granulated blast furnace slag and carbide slag powder. The chemical compositions of the four industrial solid wastes are shown in Table 1.

[0055] Step 2, take 7500g of phosphogypsum, 600g of fly ash, 900g of blast furnace slag, and 1000g of calcium carbide slag in step 1, pour them into a cement mortar mixer and stir for 10 minutes to premix to obtain a solid mixture.

[0056] Step 3, take 4100 g of tap water, 40 g of liquid polycarboxylate water reducer, and 18 g of suspension stabilizer, mix and stir for 10 minutes to obtain a liquid mixture.

[0057] Step 4, pouring the liquid mixture obtained in step 3 into a cement mortar mixer, mixing and stirring for 10 minutes, to obtain a full industrial solid waste filling material based on phosphogypsum.

[0058] Take a certain amount of filling material for setting time, fluidity and water bleeding test, transfer the remaining filling material to a cylindrical plastic mold with a diameter of 50mm and a height of 100mm, and drill a hole with a diameter of 2mm at the bottom of each mold. Then place the mold on a vibration table for 120 seconds and wrap it with plastic film. After a 24-hour pre-setting period, the sample is carefully removed from the mold and wrapped with plastic film to retain moisture. Subsequently, all samples are transferred to a laboratory with a stable temperature and humidity environment (maintained at 20±2℃ and 90±5%, respectively) for curing for 28 days.

[0059] The filling material obtained in this embodiment was tested for setting time, fluidity and water seepage rate, and the fluidity was measured to be 18.5 cm, the initial setting time was 35.0 h, the final setting time was 42.5 h, the water seepage rate was 3.53%, and the 28-day unconfined compressive strength was 3263.29 kPa.

[0060] Example 4

[0061] A method for preparing a full industrial solid waste filling material based on phosphogypsum comprises the following steps:

[0062] Step 1: Place the raw material phosphogypsum from Yichang, China in a constant temperature drying environment at 45°C, dry it, and crush it with a soil crusher to obtain phosphogypsum powder; air-dry the fly ash from Shandong, China, blast furnace slag and carbide slag from Henan, China, to obtain dry fly ash, granulated blast furnace slag and carbide slag powder. The chemical compositions of the four industrial solid wastes are shown in Table 1.

[0063] Step 2, take 8000g of phosphogypsum, 600g of fly ash, 400g of blast furnace slag, and 1000g of calcium carbide slag in step 1, pour them into a cement mortar mixer and stir for 10 minutes to premix to obtain a solid mixture.

[0064] Step 3, take 4700 g of tap water, 40 g of liquid polycarboxylate water reducer, and 18 g of suspension stabilizer, mix and stir for 10 minutes to obtain a liquid mixture.

[0065] Step 4, pouring the liquid mixture obtained in step 3 into a cement mortar mixer, mixing and stirring for 10 minutes, to obtain a full industrial solid waste filling material based on phosphogypsum.

[0066] Take a certain amount of filling material for setting time, fluidity and water bleeding test, transfer the remaining filling material to a cylindrical plastic mold with a diameter of 50mm and a height of 100mm, and drill a hole with a diameter of 2mm at the bottom of each mold. Then place the mold on a vibration table for 120 seconds and wrap it with plastic film. After a 24-hour pre-setting period, the sample is carefully removed from the mold and wrapped with plastic film to retain moisture. Subsequently, all samples are transferred to a laboratory with a stable temperature and humidity environment (maintained at 20±2℃ and 90±5%, respectively) for curing for 28 days.

[0067] The filling material obtained in this embodiment was tested for setting time, fluidity and water seepage rate, and the fluidity was measured to be 19.5 cm, the initial setting time was 40.0 h, the final setting time was 48.5 h, the water seepage rate was 4.59%, and the 28-day unconfined compressive strength was 2187.82 kPa.

[0068] Figure 1 This is a SEM image of the all-industrial solid waste filling material based on phosphogypsum prepared with a curing age of 28 days in Example 1 of the present invention, which is magnified 5000 times. Some hydrates can be observed, among which the needle-shaped ones are calcium aluminate, the irregular flocs are CSH, and the flaky ones are unhydrated phosphogypsum. The phosphogypsum is covered with a large number of AFt crystals, and products such as CSH and CASH may be blocked by AFt, resulting in a small number of these particles visible in the image. Figure 2 This is a SEM image of the all-industrial solid waste filling material based on phosphogypsum prepared with a curing age of 28 days in Example 2 of the present invention, magnified 5000 times. Some hydrates can also be observed, among which the short needle-shaped ones are calcium aluminate, and the irregular flocs are CSH and CASH.

[0069] Based on the above examples, the recommended ratios of phosphogypsum powder, fly ash powder, blast furnace slag powder and carbide slag powder are 65:17.5:7.5:10 (by mass). For the addition of water, liquid polycarboxylate water reducer and suspension stabilizer, the recommended mass ratios to the solid mixture are 35:100, 0.4:100 and 0.018:100, respectively. This ratio is considered to be the best formula for the full industrial solid waste filling material based on phosphogypsum.

[0070] It should be emphasized that the above description is only a preferred embodiment of the present invention and does not constitute a limitation of the present invention. Any simple modification, adjustment or equivalent change of the above embodiment based on the technical essence of the present invention shall be deemed to be within the protection scope of the technical solution of the present invention.

Claims

1. A full industrial solid waste filling material, characterized in that: The invention is made of a solid component and a liquid component, wherein the solid component comprises phosphogypsum, fly ash, blast furnace slag and carbide slag, and the liquid component comprises a liquid polycarboxylate water reducer, a suspension stabilizer and water; Among them: the mass ratio of phosphogypsum, fly ash, blast furnace slag and carbide slag is (65~80):(5~20):(5~20):10, the mass ratio of liquid polycarboxylic acid water reducer to solid component is 0.4:100, the mass ratio of suspension stabilizer to solid component is (0.04~0.18):100, and the mass ratio of water to solid component is (35~50):

100.

2. The full industrial solid waste filling material according to claim 1, characterized in that: The content of CaSO4·H2O in the phosphogypsum is ≥65%, and the pH value is ≤4; the content of SiO2 and Al2O3 in the fly ash is ≥80%; the content of CaO in the blast furnace slag is ≥40%, and the content of SiO2 is ≥30%; the content of CaO in the carbide slag is ≥85%, and the pH value is ≥12.

3. The method for preparing the full industrial solid waste filling material according to claim 1 or 2, characterized in that: The following steps are involved: Step 1, drying and crushing the phosphogypsum to obtain phosphogypsum powder; air-drying fly ash, blast furnace slag, and carbide slag to obtain dry fly ash, granulated blast furnace slag, and carbide slag powder; Step 2: premixing the phosphogypsum powder, fly ash, granulated blast furnace slag and carbide slag powder obtained in step 1 to obtain a solid component; Step 3, mixing a liquid polycarboxylate water reducer, a suspension stabilizer and water to obtain a liquid component; Step 4, mixing the solid component obtained in step 2 and the liquid component obtained in step 3 to obtain a full industrial solid waste filling material based on phosphogypsum.

4. The preparation method according to claim 3, characterized in that: In step 1, the phosphogypsum is dried at 45°C.

5. Use of the all-industrial solid waste filling material according to claim 1 or 2 in overburden separation filling or filling mining.